Bibliometric Analysis of Financial Technology (FinTech) and Its Implications for Financial Management - Syamsiah, Syamsiah (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to explore the development of research trends in Financial Technology (FinTech) and its implications for financial management through a bibliometric analysis approach. Data were collected from reputable international journal databases and analyzed using bibliometric tools such as VOSviewer and Publish or Perish to identify publication patterns, citation networks, influential authors, and key thematic clusters. The findings reveal a significant increase in FinTech-related publications over the past decade, with dominant research themes including digital payment systems, blockchain technology, peer-to-peer lending, risk management, and financial inclusion. Furthermore, the bibliometric mapping highlights the interconnectedness between FinTech innovation and the transformation of traditional financial management practices, particularly in enhancing efficiency, accessibility, and transparency. This study contributes to the understanding of the scientific landscape of FinTech research and provides insights for academics, practitioners, and policymakers in aligning financial management strategies with technological advancements.